1993
DOI: 10.1111/j.1469-8137.1993.tb03891.x
|View full text |Cite
|
Sign up to set email alerts
|

CO2 fluxes of cryptogamic crusts

Abstract: SUMMARYTlie carbon dioxide exchange of Mkrocoleus-and Scytonema-dom'mated cryptogamic crusts as related to dehydration was measured in the laboratory with a modified discrete sampling technique and infrared gas analysis. The dehydration curves predicted that carboxylation and dark respiration rates for both crust types would become zero at from 4 to 5 % water content (W) (approximately 16-23 % soil saturation), with the water contents at which the rates became zero significantly lower in the second treatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Instantaneous rates of carbon (C; Garcia-Pichel and Belnap 1996;Evans and Lange 2001;Jeffries et al 1993) and nitrogen (Johnson et al 2005;Abed et al 2010) fixation in BSCs during periods of microbial activity are high enough to expect noticeable long-term increases in BSC soil C and N content. However, biomass does not seem to accumulate in a commensurate manner in BSCs during succession to maturity, and loss processes are deemed to be important (Garcia-Pichel and Belnap 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Instantaneous rates of carbon (C; Garcia-Pichel and Belnap 1996;Evans and Lange 2001;Jeffries et al 1993) and nitrogen (Johnson et al 2005;Abed et al 2010) fixation in BSCs during periods of microbial activity are high enough to expect noticeable long-term increases in BSC soil C and N content. However, biomass does not seem to accumulate in a commensurate manner in BSCs during succession to maturity, and loss processes are deemed to be important (Garcia-Pichel and Belnap 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Such a phenomenon can also be observed in the field, where the greening occurs after long rainy and cloudy conditions. In these environments, the water potential obviously plays a key role in the control of growth and activity of microorganisms [3,6,15]. Recently, we have shown that cyanobacteria in desert soils can track water, suggesting that cyanobacterial migration was controlled by the water content [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies [22][23][24][25] have focused mainly on structure, distribution, nitrogen fixation or work with isolated cultures. Despite their importance only a few studies are interested in the ecophysiology of cyanobacterial crust communities of the tropical and subtropical inselberg rock surfaces [7,9,19,21,[26][27][28] and seasonally inundated system of plans and dunes [29,30]. Most studies deal with the photosynthesis of the cryptogamic crusts under laboratory conditions [29] while only few characterize the photosynthesis of free-living cyanobacteria under natural conditions in the tropical field [7,21,28,31] and desert [11,13,30].…”
Section: Introductionmentioning
confidence: 99%